Produção de cerveja, utilizando méis de diferentes origens botânicas como adjuntos - Mansano, Alexandre Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study aimed to produce beer, using different botanical origins of honeys (orange, eucalyptus and wild), as malt adjuncts, and their Physical-chemical and sensorial characterizations. The production was made with malt, water, hops and honey. All musts were adjusted to 12 Brix, and the concentration of honey in the formulation was 45% (based on the extract), except for the control (0%). The physical and chemical analysis were performed on malt (extract content), honey (pH, free acidity, lactonic acidity, total acidity, color, turbidity, extract content, moisture content, reducing sugar, total reducing sugar and sucrose) in wort (content extract, pH, color, turbidity, fermentability ,bitterness and total acidity) and beer apparent extract, apparent fermentability, real extract, real fermentability, alcohol content, pH, total acidity, total foam, foam density , bitterness, carbon dioxide, color and turbidity). Sensory analysis was performed by nine-points hedonic scale testing. The attributes evaluated were appearance, aroma, flavor and overall. The results were submitted to ANOVA and means compared by Tukey testing at a 5% of probability. Beer with honey as adjuncts’ had high fermentability and low content of fat, compared to the pure malt beer. The addition of honey as an adjunct did not affect the majority of the physical-chemical parameters, except for turbidity, whereas beer with honey showed the highest value for this feature, in addition, it has also presented their biterness differences the values for beer with honey were lower. The different types of honeys did not affect the acceptability of beer, however, the beer with honey showed greater acceptance between beer with malt and honey

O presente trabalho teve como objetivo a produção de cerveja, utilizando méis de diferentes origens botânicas (laranjeira, eucalipto e silvestre), como adjuntos de malte, e suas caracterizações físico-químicas e sensoriais. A produção foi feita com malte, água, lúpulo e mel. Todos os mostos foram corrigidos para 12 Brix, e a concentração de mel na formulação foi de 45% (com base no extrato), exceto a testemunha (0%). As análises físico-químicas foram realizadas no malte (teor de extrato), no mel (pH, acidez livre, acidez lactônica, acidez total, cor, turbidez, teor de extrato, umidade, açúcar redutor, açúcar redutor total e sacarose), no mosto, (teor de extrato, pH, cor, turbidez, fermentabilidade e amargo, acidez total), e na cerveja (extrato aparente, fermentabilidade aparente, extrato real, fermentabilidade real, teor alcoólico, pH, acidez total, espuma total, espuma densidade, amargor, gás carbônico, cor e turbidez). A análise sensorial foi realizada pelo teste de escala hedônica estruturada de nove pontos. Os atributos avaliados foram: aparência, aroma, sabor e avaliação geral. Os resultados foram submetidos à análise de variância, e as médias comparadas pelo teste de Tukey a 5% de probabilidade. A cerveja com méis como adjuntos apresentam alta fermentabilidade e baixo teor de extrato, quando comparada à cerveja puro malte. A adição de mel como adjunto não interferiu na maioria das características físico-químicas avaliadas, exceto para turbidez, na qual a cerveja com méis apresentou maior valor para essa característica; além disso, o amargor também apresentou diferenças, sendo que seus valores para a cerveja com mel foram menores. Os diferentes tipos de méis não interferiram na aceitabilidade da cerveja, no entanto, a cerveja com mel silvestre possuiu maior aceitação entre as cervejas com méis e a puro malte
Keywords: Malte; Fermentação - Controle de qualidade; Cerveja; Alcoholic Fermentation; Malt; Sensory Analysis